The Effectiveness of English Talkshow Program on Students’ Speaking Ability at STKIP PGRI Bangkalan - Mustain (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2016)
This study is to know the effect of Talkshow Program on speaking ability at the students of English Department at STKIP PGRI Bangkalan. This study is true-experimental focused on Randomized Posttest only control group design. The population was 167 students selected randomly as a sample was 60 students, then was assigned randomly to experimental group and control group each 30 students. The data collected was from performance test individually and analyzed then by Independent T-test by the level of significance 5% through SPSS 22. As a result, t value > t critical (45.557>2.034); so H0 is rejected and Ha is accepted. It meant that, there is a significant different between the students’ speaking ability with English talkshow Program and with non- English talkshow Program.. In conclusion, mean of the speaking ability between both programs is significant difference by seeing the mean difference is 18.66667. the result showed that the students are taught by English Talkhsow Program perform better in speaking ability than those taught with non-English talkshow program.